2021
DOI: 10.1021/acs.inorgchem.1c02536
|View full text |Cite
|
Sign up to set email alerts
|

An Organic-Inorganic Hybrid Pyrrolidinium Ferroelectric Based on Solvent Selective Effect

Abstract: Organic-inorganic hybrid ferroelectrics (OIHFs) have fueled enormous interest benefiting from their less environmental pollution, performance-tailored functionality, low product costs as well as tunability of structures. However, the lack of material synthesis approaches and diverse targeted molecular design is a stumbling block for designing novel OIHFs rationally. Here, we report a unique organic-inorganic hybrid ferroelectric (3,3-difluoropyrrolidine)2CdCl4 1 and another novel nonferroelectric crystal (3,3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…32 In addition, Jiao et al also reported a H/F-substituted HOIF (C 4 H 8 NF 2 ) 2 CdCl 4 , in which two different solvents were used to obtain a ferroelectric and a non-ferroelectric. 33 At present, the number of zinc-based ferroelectrics is still relatively small. Inspired by these studies, we used 3,3-difluoropyrrolidine hydrochloride and ZnCl 2 to obtain a (3,3-difluoropyrrolidine) 2 ZnCl 4 •H 2 O (DFZC) crystal by the solution evaporation method with water as a solvent.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 In addition, Jiao et al also reported a H/F-substituted HOIF (C 4 H 8 NF 2 ) 2 CdCl 4 , in which two different solvents were used to obtain a ferroelectric and a non-ferroelectric. 33 At present, the number of zinc-based ferroelectrics is still relatively small. Inspired by these studies, we used 3,3-difluoropyrrolidine hydrochloride and ZnCl 2 to obtain a (3,3-difluoropyrrolidine) 2 ZnCl 4 •H 2 O (DFZC) crystal by the solution evaporation method with water as a solvent.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Another example is that Wu et al synthesized zinc-based chiral hybrid organic–inorganic RMPZnS 2 and SMP 2 ZnS 3 single crystals, in which the RMPZnS 2 crystal is ferroelectric . In addition, Jiao et al also reported a H/F-substituted HOIF (C 4 H 8 NF 2 ) 2 CdCl 4 , in which two different solvents were used to obtain a ferroelectric and a non-ferroelectric . At present, the number of zinc-based ferroelectrics is still relatively small.…”
Section: Introductionmentioning
confidence: 99%
“…However, very little attention was paid on the effect of difluoride substitution on the spacer cations of 1D chain HOIPs. In fact, difluoride substitution on the 1D HOIPs has a chance to result in the dimensional increment to 2D HOIPs, such as (3,3-difluoropyrrolidine) 2 CdCl 4 , (4,4-DFHHA) 2 PbI 4 , and (4,4-DFPD) 2 PbI 4 . The expansion of the Pb–I network from 1D to 2D for lead iodide HOIPs usually leads to the band gap reduction, which is of great importance for their photoelectric feature. , …”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 2 , 3 ] Combined with their excellent pyroelectric, piezoelectric, and other physical properties, ferroelectrics represented by the inorganic ceramics such as barium titanate (BTO) and lead zirconate titanate (PZT) have been widely used for electronic applications, such as transducers, memories, actuators, and sensors. [ 4 , 5 , 6 , 7 ] Facing the challenges of the environment, energy, and cost, the focus of materials science has gradually but firmly shifted from inorganic and organic–inorganic systems to organic ones. [ 8 ] Recently, interest in organic ferroelectrics is increasing because of their superiority of lightweight, good degradability, easy solution processing, low acoustic impedance (matches with human bodies), satisfying biocompatibility, and environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%